Perempuan Dalam Skena Musik Undeground di Kota Bekasi - Amelia, Amelia; Koodoh, Erens E (JURNAL KABANTI: Kerabat Antropologi, 2025)
This research aims to analyze the involvement of women in underground music in Bekasi City and the obstacles faced by women in accessing and developing in underground music. This research uses Peter L. Berger's social construction theory. The method used in this research is a qualitative method, where data collection uses observation techniques and in-depth interviews.The results of this study indicate that women choose to participate in underground music as a form of self-expression and rebellion against social norms that limit their roles. Female musicians, such as Harin and Naomi, challenge gender stereotypes by becoming vocalists in underground bands, demonstrating that women deserve recognition in a music industry often seen as a male domain. Moreover, women in the underground music scene face various obstacles, including negative stereotypes that perceive them as unfit for the community. This study concludes that the involvement of women in underground music in Bekasi is a form of resistance to gender norms and demonstrates that underground music is becoming more inclusive and diverse.